KEARIFAN LOKAL TRI HITA KARANA DALAM PROGRAM CORPORATE SOCIAL RESPONSIBILITY - Yeni Rosilawati; Krisna Mulawarman (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2019)
Extant research has confirmed that influence of local factors (social, cultural, political and economic) on the implementation of CSR across worldwide. The rise of conflict between firms and communities emphasizes the understanding of socio-cultural aspects in the context of communities. This study aimed to explore the effects of Tri Hita Karana local wisdom on the CSR initiatives through a case study in Aqua Danone, Bali. This study has employed a qualitative paradigm where in-depth interviews were conducted with local community members, local community leaders, NGO employees, and managers who are involved with CSR initiatives and strategies on daily basis. Secondary data such reports about CSR programs were also employed in this study. The finding shows that local wisdom of Tri Hita Karana (THK) that integrated worship, man and nature has been adopted as a CSR guidance and appears across all levels of CSR starting from the program planning phase and going through the preparation of strategies until the process of implementation and control. This study also concluded that CSR program should consider local forums such as sangkep (routine meeting held by the village) and the enforcement of local rules (pararem) to engage the local communities to run it sustainably. This research recommends the application of local wisdom relevant to CSR implementation.